Getting physicians to open the survey: little evidence that an envelope teaser increases response rates - Ziegenfuss, Jeanette Y (BioMed Central, 2012)
BACKGROUND: Physician surveys are an important tool to assess attitudes, beliefs and self-reported behaviors of this policy relevant group. In order for a physician to respond to a mailed survey, they must first open the envelope. While there is some evidence that package elements can impact physician response rates, the impact of an envelope teaser is unknown. Here we assess this by testing the impact of adding a brightly colored "$25 incentive" sticker to the outside of an envelope on response rates and nonresponse bias in a survey of physicians. METHODS: In the second mailing of a survey assessing physicians' moral beliefs and views on controversial health care topics, initial nonrespondents were randomly assigned to receive a survey in an envelope with a colored "$25 incentive" sticker (teaser group) or an envelope without a sticker (control group). Response rates were compared between the teaser and control groups overall and by age, gender, region of the United States, specialty and years in practice. Nonresponse bias was assessed by comparing the demographic composition of the respondents to the nonrespondents in the experimental and control condition. RESULTS: No significant differences in response rates were observed between the experimental and control conditions overall (p = 0.38) or after stratifying by age, gender, region, or practice type. Within the teaser condition, there was some variation in response rate by years since graduation. There was no independent effect of the teaser on response when simultaneously controlling for demographic characteristics (OR = 0.875, p = 0.4112). CONCLUSIONS: Neither response rates nor nonresponse bias were impacted by the use of an envelope teaser in a survey of physicians in the United States.